A novel approach to account for shape-morphing and kinetic shading systems in building energy performance simulations - Carlucci, Francesco; Loonen, Roel C.G.M.; Fiorito, Francesco; Hensen, Jan L.M. (Journal of building performance simulation, 2023)
This paper proposes an innovative approach to analyse the energy behaviour of complex kinetic shading systems. Although several studies have analysed this topic, many are focused only on certain aspects or on simple shading systems due to a lack of tools for running reliable energy simulations on complex systems. This study aims to develop and validate a tool based on Python and EnergyPlus that can consider the continuous nature of the energy simulation and analyse complex kinetic systems. Simply providing an EnergyPlus model and a model of the shading configurations, the algorithm provides as output a comparison sheet to evaluate the performance of the system. The paper provides a description of the tools and studies focused on this topic; subsequently, a methodological insight is presented to explain the workflow, its validation, and the algorithm developed. Finally, the algorithm is tested on a case study to analyse a kinetic shading system. Abbreviations: DSF: Dynamic Shading File; EDSM: Equivalent Dynamic Shading Model; EMS: Energy Management System; ESSM: Equivalent Static Shading Model; Gf: Incident irradiance; Gf max: Incident irradiance threshold; PV: Photovoltaic; ST1/2/3: State 1/2/3; SSM: Static Shading Model; SF: Sunlit Fraction; SSF: Static Shading File; To: Outdoor temperature; To max 1/2: Outdoor temperature threshold 1/2; Tsol: Solar transmittance